MULTIMEDIAS ET LANGUE DE SPECIALITE - Vougiouklidou, Anna (European Scientific Journal, ESJ, 2013)
The department of IT is the department where the teachers and the students’ roles are reverse. This is what we found at the University of Piraeus where the students who attend the lesson of the French language as a language of specialty are not only familiar with the multimedia, but they are also almost professionals. The students of this department are more prompt to take initiative in comparison with other departments of the University and the teacher functions more like a consultant. He will illustrate to the students that he familiarizes them with the terminology of their science and the enhancement of their language skills, in general, recommending various websites the can visit.